The Middle Ages in texts and texture : reflections on Medieval sources - Glenn, Jason, 1967-; Brentano, Robert, 1926-2002 (University of Toronto Press, 2011)
"The Middle Ages in Texts and Texture is an introduction to medieval Europe unlike any other. These 26 essays, written by accomplished scholars all trained at the University of California, Berkeley, reflect on medieval texts and the opportunities they present for exploration of the Middle Ages. Introduced in a foreword by Thomas N Bisson (Harvard University) these essays present a textured picture of the medieval world and offer models for how to reflect fruitfully on medieval sources. To help orient the reader, three maps, the editor's introduction, and an index are provided."--P [4] of cover